APPLICATION AND PERSPECTIVE OF OPEN ENDED APPROACH TO STUDENT LEARNING OUTCOMES IN BUSINESS MATH SUBJECT - Azis, Yunia Mulyani (Advances in Social Sciences Research Journal, 2018)
This research was conducted with the aim to apply open ended approach in business mathematics course in order to increase learning outcomes, but also to see the perspective of students after the open ended approach implemented. The population of this research is STIE Ekuitas students who are taking business math course, while the sample is selected by purposive sampling as many as 81 people (2 classes). The results of the assessed study consisted of 3 (three) components of the ability of conceptual skills, procedural, and problem-solving skills. Preparations and postest are given in the form of a description consisting of 10 (ten) questions, while to see the perspective of students used 9 (nine) items. Testing is done using t-test and MANOVA. The conclusions of this research are (1) there are significant differences in ability between students who are given mathematics learning using open ended and conventional students, especially conceptual, procedural, and problem solving skills; (2) the use of open ended can strengthen the knowledge of students in thinking of mathematics, as an effort to solve problems, and (3) open ended enables students to interact with their friends through discussion, so that students can gain knowledge about mathematics more broadly.